Oscillations and control of spherical parallel manipulator. (8th May 2019) - Nhan, Nguyen Huu Khanh; Tung, Vo Dinh; Kheylo, Sergey; Victor, Glazunov
In recent years, there has been a growing number of studies in spherical parallel mechanisms, particularly synthesis, kinematics, and work area singularities. The interaction of degrees of freedom and geometry leads to the nonlinear phenomena, in the dynamics of mechanism. There are few studies into the dynamic properties of such mechanisms. This article deals with the dynamic property of the parallel spherical manipulators, with three degrees of freedom, and presents determination of acceleration input links, oscillations, and the problem of control. Algorithm of control is based on the concept of minimized coordinates, velocities, and acceleration using inverse dynamic problems. This allows synthesis of this algorithm, which can realize a motion in accordance with prescribed trajectories. Finally, the results of calculations are defined.